2003
DOI: 10.1093/cercor/bhg093
|View full text |Cite
|
Sign up to set email alerts
|

Cortex, Cognition and the Cell: New Insights into the Pyramidal Neuron and Prefrontal Function

Abstract: Arguably the most complex cortical functions are seated in human cognition, the how and why of which have been debated for centuries by theologians, philosophers and scientists alike. In his best-selling book, An Astonishing Hypothesis: A Scientific Search for the Soul, Francis Crick refined the view that these qualities are determined solely by cortical cells and circuitry. Put simply, cognition is nothing more, or less, than a biological function. Accepting this to be the case, it should be possible to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
332
0
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 390 publications
(347 citation statements)
references
References 175 publications
11
332
0
4
Order By: Relevance
“…While it is well known that neuron structure determines its biophysical properties (Koch, 1999), it is less well known how neuron structure may influence the functional properties of the circuits they compose. It is our contention that cortical circuits composed of pyramidal cells of different structure will be characterized by different functional capabilities, much in the same way that artificial systems composed of highly interconnected and powerful processors differ in their functional abilities to those composed of less powerful processors with fewer connections (for review, see Elston, 2003a). Several direct examples of the structure-function relationship have been demonstrated between pyramidal cell structure and cortical function.…”
Section: Structure/function Relationshipmentioning
confidence: 99%
See 3 more Smart Citations
“…While it is well known that neuron structure determines its biophysical properties (Koch, 1999), it is less well known how neuron structure may influence the functional properties of the circuits they compose. It is our contention that cortical circuits composed of pyramidal cells of different structure will be characterized by different functional capabilities, much in the same way that artificial systems composed of highly interconnected and powerful processors differ in their functional abilities to those composed of less powerful processors with fewer connections (for review, see Elston, 2003a). Several direct examples of the structure-function relationship have been demonstrated between pyramidal cell structure and cortical function.…”
Section: Structure/function Relationshipmentioning
confidence: 99%
“…Several direct examples of the structure-function relationship have been demonstrated between pyramidal cell structure and cortical function. For example, differences in the size of the dendritic trees of pyramidal cells potentially influence topographic sampling strategies and mixing of inputs (Jacobs and Scheibel, 2002;Elston, 2003a). Differences in the branching complexity in the Fig.…”
Section: Structure/function Relationshipmentioning
confidence: 99%
See 2 more Smart Citations
“…11 Comparative studies of pyramidal neurons in granular prefrontal cortex have shown that human neurons display much larger dendritic trees and, on average, up to 20 times as many dendritic spines as those in the primary cortexes. 12,13 The maintenance of such dendritic complexity probably requires high levels of energy consumption. 14 We thought that SLC25A12 expression might be modified in prefrontal cortex pyramidal neurons in adult brain.…”
Section: Introductionmentioning
confidence: 99%